A case of right-sided congenital subclavian steal - Dainton, Christopher J (Pulsus Group Inc, 2010)
A 21-year-old man presented with an uncommon asymptomatic case of right-sided congenital subclavian steal. On physical examination, his blood pressure was 115/80 mmHg in the left arm, but could not be measured in the right arm. Magnetic resonance angiography demonstrated that the origin of the right subclavian artery was atretic, and supplied by a number of collaterals near the origins of the internal mammary and vertebral arteries. Subclavian steal should be a diagnostic consideration in any patient who presents with a pulse deficit or a systolic blood pressure difference of greater than 15 mmHg. A description of the acquired and congenital varieties of subclavian steal is provided.